Mobile anchor assisted localization and path-planning techniques in wireless sensor networks: Challenges and Solutions. Issue 2 (March 2019) - Long, Yuxuan; Liang, Junbin
Abstract: Localization is one of the most significant technique in wireless sensor networks (WSNs). The location information of nodes can be provided by Global Positioning System (GPS), but the cost is huge if every node equips GPS. This problem can be solved by deploying a set of mobile anchors which can exchange information with other nodes that estimating their locations. Planning an adaptive path can reduce the cost by using smaller number of mobile anchors and estimate the location of other nodes precisely in WSNs. In recent years, many path planning algorithms have been proposed. In this paper, a comprehensive survey is presented to point out key problems and challenges of mobile anchors. We compare the differences among the algorithms. Also, we make a discussion for future research and show new challenges in this field.